Relationship between distributed leadership, teacher collaboration and organizational innovativeness - Ömür Çoban; Ramazan Atasoy (Institute of Advanced Engineering and Science, 2020)
The aim of this study was to examine the relationships between distributed leadership, organizational innovativeness and teacher collaboration. We used Turkish teacher data and conducted the analysis from teachers’ perspectives working in secondary schools in Turkish Ministry of National Education at the International Standard Classification of Education 2 (ISCED) level. In this quantitative study, we analysed the three hypotheses via structural equation model. The hypotheses assumed that there was a relationship between distribute leadership and organizational innovativeness, also there was a relationship between distrubitive leadership and teacher collaboration. Additionally, there was a relationship between teacher collaboration and organizational innovativeness. Finally, we analysed the impact of distributed leadership on organizational innovativeness via teacher collaboration. The finding indicated that there were relations between distributed leadership and organizational innovativeness. The other result showed that teacher collaboration affected organizational innovativeness. The last finding displayed that distributed leadership impacted organizational innovativeness via teacher collaboration. In conclusion, if school principals exhibited distributed leadership behavior, they would create a supportive and collaborative climate for teachers and they also encourage teachers’ agreement to develop new ideas for teaching, their openness to change, their problem-solving strategies and exchanging atmosphere where they share their practices with each other.